Energy efficient building : the application of thermal energy storage (TES) for cooling load reduction - Tee, Swee Yin (2008)
A typical building zone designated as Zone PPU, in UTHM was selected for a detailed study of applying Thermal Energy Storage (TES) for cooling load reduction. Data of electricity bills from May 2005 to December 2007 were collected for analysis of usage trending. The energy consumption index for Zone PPU was also established and compared with MS 1525 standard. The energy simulation program TRACE 700 was used to calculate the peak cooling loads for Zone PPU. Two storage systems using ice storage technology were being proposed in this study, which are full storage system and partial storage system. Two economical analysis tools, which are the Simple Payback Period method and Net Present Value method, were used to evaluate whether the proposals are economically viable to be considered. The energy consumption for buildings G 1, G2 and G3 ( of total :floor areas 15,285 m2) for the year 2007 was 7,261,803kWh, giving an energy consumption index of 475kWh/ni per year which was far too much compared to the recommended value of l 35kWh/m2 per year as stated in MS 1525 Standard. The analysis results indicated that the TES proposals for the existing cooling load of 1160RT has no attractive payback period and results negative net present value calculating up to the life span ( of 15 years) of chillers with proper maintenance, indicating that the TES proposal is not economically viable. In view of the available market references, cooling load of 3000RT and above is required in order to achieve a more economically viable proposal. Therefore, several proposals with proposed capacity ranging from 2200RT, 2900RT, 3600RT and 4200RT have been made so that the most optimum load can be selected for future considerations